2014
DOI: 10.1186/1471-2318-14-44
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Brief Ageing Perceptions Questionnaire (B-APQ): a confirmatory factor analysis approach to item reduction

Abstract: BackgroundThis paper aimed to develop a short version of the 32-item Ageing Perceptions Questionnaire (APQ), a multi-dimensional measure based on Leventhal's self-regulation model. Ageing perceptions are a key area of interest for large-scale surveys of ageing populations. As these studies capture a broad range of health and social variables, included instruments need to be as concise as possible.MethodsData from the Irish Longitudinal Study of Ageing (TILDA), a representative sample of community-dwelling indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 21 publications
(45 reference statements)
4
86
1
4
Order By: Relevance
“…As stressed by Goetz et al [12], and adopted or endorsed by other authors [29][30][31], the shortening process should preserve the conceptual model and as best possible retain the content of the original (long) instrument. In this work, the primary concern of content validity led us to "favor experts over statistics" for the selection of items, making each decision to reject or to keep an item according to relevance to the construct measured.…”
Section: Other Psychometric Propertiesmentioning
confidence: 98%
“…As stressed by Goetz et al [12], and adopted or endorsed by other authors [29][30][31], the shortening process should preserve the conceptual model and as best possible retain the content of the original (long) instrument. In this work, the primary concern of content validity led us to "favor experts over statistics" for the selection of items, making each decision to reject or to keep an item according to relevance to the construct measured.…”
Section: Other Psychometric Propertiesmentioning
confidence: 98%
“…This study found that the dimension of Timeline Chronic scored lower and obviously had an impact on both PCS and MCS. It is negatively associated with PCS, as reported by Sexton et al 39 As growing older and their health declining, patients adopt aging gradually, 40,41 which resulted in decreased PCS. In contrast, the score of Timeline Chronic was positively associated with MCS.…”
Section: Timeline Chronicmentioning
confidence: 87%
“…Araştırmacılar tarafından yapılan literatür 3,4,17,20 taraması doğrultusunda hazırlanmış olan form; yaşlı bireylerin, yaş, cinsiyet, medeni durum, eğitim düzeyi gibi sosyo-demografik özelliklerini içeren 11 sorudan oluşmaktadır. Barker…”
Section: Kişisel Tanıtım Formuunclassified
“…Ancak, ülkemizde yaşlanma kavramının yaşlılar tarafından nasıl algılandığını yani diğer bir ifadeyle subjektif yaş algısını değerlendiren geçerli ve güvenilir bir ölçme aracına rastlanmamıştır. Bu araştırmanın amacı Türk toplumundaki yaşlı bireylerin yaşlılığı nasıl algıladığını değerlendirmek için Sexton ve arkadaşları (2014) 17 tarafından geliştirilen "Yaşlılığı Algılama Anketi Kısa Formu"nun Türk toplumu için geçerlilik ve güvenirlik çalışmasının yapılmasıdır. Yaşlılığın ülkemizdeki yaşlılar için taşıdığı anlam ve bu yaşlıların toplumdan beklentilerinin objektif ölçüm araçlarıyla belirlenmesi pozitif yaşlılık algısı geliştirmek için yapılacak olan çalışmalar için veri kaynağı olacaktır.…”
Section: Introductionunclassified